Iron Absorption and its Influencing Factors to Prevent Iron Deficiency - Dilantika, Charisma (Journal of Indonesian Specialized Nutrition, 2023)
Iron is an important nutrient, required to support tissue oxygen delivery, cell growth and differentiation regulation, and energy metabolism. Body iron levels are mainly controlled by regulation of iron absorption in duodenum and proximal jejunum, allowing absorption to be accurately matched to unregulated losses. Since iron bioavailability often reduced, dietary iron absorption is controlled by cellular and systemic factors to ensure that overall body iron levels are maintained at adequate levels. A better understanding of the mechanism for iron absorption and factors influencing its absorption and bioavailability is important to avoid iron deficiency or iron overload. There are complex regulatory frameworks managing iron absorption, transportation, storage, and recycling. It is able to provide enough iron for critical body functions and react relatively quickly as iron demands increase, but mechanisms must also be in place to restrict iron absorption once the body is overwhelmed with iron. Several factors promote and impede iron absorption, such as phytate and ascorbic acid, respectively. The danger of iron deficiency for the world's population is of great significance, it is important to introduce effective strategies to tackle this issue through nutrition programs; food iron supplements; iron medication supplements; and probiotic, prebiotic, and symbiotic approaches.